Identification of the Effectiveness of Clustering (Rayonisasi) System in an Effort to Evenly Distribute Accessibility towards High School Education Facilities in Bandung City - Roos Akbar; Muhammad Amri Cahyo; Farida Khuril Maula (The Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
Abstract. Based on Mayoral Decree No. 610 Year 2016 on the Procedure of New Students Admissions (PPDB), the municipal government of Bandung uses a clustering system for the process of student admission. This research was aimed at producing a description of issues related to school capacity and the mapping of school facility distribution based on quality. This is considered important in order to be able to see the capability of Bandung's clustering policy to give the school age population a chance to obtain qualified education. This research used a descriptive spatial analytical method with the GIS application to analyze the adequacy of state high school capacity in Bandung using weighting to determine the distribution of state high school quality in Bandung. The spatial analysis could determine the distribution of state high school facility locations in Bandung, the scope of state high school service areas based on district division, the number of the school age population within the area of the facilities, the number of the school age population that is not accommodated by a school, and the mapping of state high school quality based on passing grade score, the average national examination score, and school accreditation score. The comparison of high school capacity and quality in Bandung showed that the clustering policy does not pay attention to these two aspects comprehensively. From the capacity side, the area of Bandung City that is within the scope of state high school facilities is only 79.25% with a total of 169,538 students school age students living in this area. However, the total capacity of state high school facilities in Bandung is only 30,751 students. As for the quality aspect, highly qualified state high schools tend to be located in the center of Bandung while low quality high schools tend to be located in the fringe areas.Keywords. State high school facilities, clustering, capacity, quality, effectiveness, geographic information system.Abstrak. Berdasarkan Keputusan Walikota Bandung No. 610 Tahun 2016 tentang Tata Cara Penerimaan Mahasiswa Baru (PPDB), Pemkot Bandung menetapkan sistem rayonisasi dalam proses penerimaan mahasiswa baru. Penelitian ini bertujuan untuk menghasilkan gambaran masalah yang berkaitan dengan kapasitas sekolah dan pemetaan distribusi fasilitas sekolah berdasarkan kualitas. Hal ini dianggap penting untuk melihat kemampuan kebijakan rayonisasi di Bandung dalam memberikan kesempatan bagi populasi usia sekolah untuk memperoleh layanan pendidikan yang berkualitas. Penelitian ini menggunakan metode analisis spasial deskriptif dengan aplikasi GIS untuk menganalisis kecukupan kapasitas sekolah dengan menggunakan metode weighting untuk mengetahui distribusi kualitas SMA negeri di Bandung. Analisis spasial dengan menggunakan aplikasi GIS dapat menentukan distribusi lokasi fasilitas SMA negeri di Bandung, ruang lingkup pelayanan SMA negeri berdasarkan pembagian kabupaten, jumlah penduduk usia sekolah di wilayah pelayanan fasilitas, jumlah populasi usia sekolah yang tidak tertampung di sekolah, dan pemetaan kualitas SMA negeri berdasarkan nilai kelulusan, skor rata-rata ujian nasional, dan skor akreditasi sekolah. Perbandingan kapasitas dan kualitas SMA di Bandung menunjukkan bahwa kebijakan rayonisasi belum memperhatikan dua aspek secara komprehensif. Dari sisi kapasitas, luas Kota Bandung yang berada di dalam jangkauan layanan sekolah hanya 79,25% dengan jumlah total 169,538 siswa yang tinggal di daerah tersebut. Namun, kapasitas SMA Negeri di Bandung hanya 30.751 siswa, sedangkan dari sisi kualitas, SMA negeri yang berkualitas cenderung ditempatkan di pusat kota Bandung, sedangkan sekolah dengan kualitas rendah cenderung ditempatkan di daerah pinggiran kota.Kata Kunci: fasilitas SMA Negeri, rayonisasi, kapasitas, kualitas, efektifitas, sistem informasi geografis